The Role of the Property Unit (Harda) in the Criminal Investigation Unit of the South Sumatra Police South Sumatra in Eradicating the Land Mafia in South Sumatra - Mayangsari*, Riska; Yusuf, Hambali; Salia, Erli; Mahfuz, Abdul Latif (Riwayat: Educational Journal of History and Humanities, 2023)
This paper discusses the role of the Property Unit (HARDA) of the South Sumatra Police Criminal Investigation Unit in eradicating the existence of the land mafia in South Sumatra. The land mafia has become a serious threat to the order and justice of land ownership, resulting in legal uncertainty and harming the wider community. HARDA plays a critical role in identifying, investigating and taking legal action against perpetrators of the land mafia. Through in-depth interviews, documentation, and field data analysis, this research explores HARDA's strategies, methods, and challenges. The results showed that HARDA managed to identify and handle a number of cases effectively, but there were still obstacles in cross-sector coordination and limited resources. Recommendations were put forward to strengthen HARDA's capacity and enhance cooperation with other relevant entities to achieve more optimal results in eradicating the land mafia.